Leaving the Countryside: Rural-to-Urban Migration Decisions in China - Zhao, Yaohui (American Economic Review, 1999)
This paper employs a simple theoretical model of labor allocation within rural households given existing land arrangements in an attempt to explain why rural Chinese do not fully participate in labor migration. It first explores the mechanisms by which individual household and community characteristics affect the migration decision. Empirical results are then presented to substantiate the derived hypotheses. The paper further explores the question of whether the migration decision is permanent by analyzing the responses of household consumption to income from migration. (EXCERPT)